Analysis of protein folding equilibria by nano‒electrospray‒ionization mass spectrometry. Issue 3 (2002) - Matecko Matecko, Irena Irena; Müller Müller, Norbert Norbert; Grandori Grandori, Rita Rita
Abstract : This paper summarizes recent findings from our group concerning applications of electrospray‒ionization mass spectrometry (ESI‒MS) to the study of protein folding. Nano‒ESI‒MS was employed for the investigation of protein conformational states under varying solvent conditions and at varying values of the instrumental parameters. The effect of trifluoroethanol (TFE) on a peptide and acid‒unfolded cytochrome c (cyt c ), monitored by circular dichroism (CD) and time‒of‒flight ESI‒MS, illustrates the specificity of the latter technique for features of protein tertiary structure. Measurements on marginally stable protein states indicate that it is possible to identify operational conditions for nano‒ESI‒MS in which none of the instrumental parameters limits conformational stability in the protein sample. Results described here show that changes in the charge‒state distributions (CSDs) under controlled conditions allow not only discriminating between native and denatured states, but also monitoring minor conformational changes, like the transition from molten globule to native state. These studies underscore the potential of mass spectrometry methods for the analysis of heterogeneous samples and, in particular, for the characterization of dynamic equilibria involving different conformational states.